Southern African governments implement policy change towards climate-smart, sustainable smallholder farming systems - CGIAR Research Program on Maize (2021)
Climate-smart agriculture mainstreamed in Zimbabwe’s National Agriculture Policy Framework, Climate Change Response Strategy; similarly for Zambia, including its Disaster Management Policy and Malawi. Adopted on 627,000 ha by 3M+ farmers.